Ethnic patriotism and the East African Revival : a history of dis sent, c. 1935 to 1972 - Peterson, Derek R., 1971- (Cambridge : Cambridge University Press, 2012)
"This book focuses on the struggle between cosmopolitan Christian co nverts and east African patriots to define culture and community in the mid-twentieth century"--
"Ethnic Patriotism and the East African Revival shows how, in the er a of African political independence, cosmopolitan Christian converts st ruggled with east Africa's patriots over the definition of culture and community. The book traces the history of the East African Revival, an evangelical movement that spread through much of eastern and central Af rica. Its converts offered a subversive reading of culture, disavowing their compatriots and disregarding their obligations to kin. They earne d the ire of east Africa's patriots, who worked to root people in place as inheritors of ancestral wisdom. This book casts religious conversio n in a new light: not as an inward reorientation of belief, but as a po litical action that opened up novel paths of self-narration and unsettl ed the inventions of tradition"--
Machine generated contents note: List of Illustrations; Acknowledgme nts; 1. Introduction: the pilgrims' politics; 2. The infrastructure of cosmopolitanism; 3. Religious movements in southern Uganda; 4. Civil so ciety in Buganda; 5. Taking stock: conversion and accountancy in Bugufi ; 6. Patriotism and dissent in western Kenya; 7. The politics of moral reform in northwestern Tanganyika; 8. Subjects of the law: conversion a nd court procedure; 9. Casting characters: autobiography and political argument in central Kenya; 10. Confession, slander, and civic virtue in Mau Mau detention camps; 11. Contests of time in western Uganda; Concl usion: pilgrims and patriots in contemporary east Africa; Bibliography.
Includes bibliographical references (pages 295-334) and index.
Keywords: Christianity and politics -- Africa, East -- History -- 20th century .; East Africa Revival -- History; Conversion -- Christianity; Christianity and culture -- Africa, East; Africa, East -- Church history -- 20th century